SEJARAH PERKEMBANGAN PONDOK PESANTREN DAR EL-HIKMAH PEKANBARU (1991-2016) - Masnur Afika Rizaxi; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Dar El-Hikmah Islamic Boarding School is one of boarding school in Pekanbaru, Background of Dar El-Hikmah Islamic Boarding School is the requirement of the use of Dar El-Hikmah Islmaic Boarding School Pekanbaru that is H. Abdullah for charity and is already a dream- from long time to establish Islamic educational institutions in the city of Pekanbaru. The initial effort of H. Abdullah to establish a boarding school in the city of Pekanbaru is to send the son of Riau to study to boarding schools in Java, then because H. Abdullah often met with various boarding schools visited, H. Abdullah get Help from the boarding school institution he met to establish a boarding school in Pekanbaru as an alternative education for the son of Riau for Islamic religious education. The purpose of this study is 1. To find out how the development of education in Dar El-Hikmah Islamic Boarding School Pekanbaru (1991-2016), 2. To find out what achievements obtained Dar El-Hikmah Islamic Boarding School Pekanbaru, 3. To know what education system applied in Dar El-Hikmah Islamic Boarding School, 4. What are the inhibiting factors and support of Dar El-Hikmah Pesantren Islamic Boarding School in developing. This research uses descriptive qualitative research method. The result of this study is a significant development occurred in Dar El-Hikmah Islamic Boarding School from its inception until today. With the achievements to be proud of and also a good education system in Dar El-Hikmah Islamic Boarding School also contributes in the field of education in the city of Pekanbaru in particular and Indonesia in general. Nothing is in progress because the ability of pesantren in accepting the progress of the times is also very good. Education Education Indonesia is still in step by step to implement a better system, this is because Indonesia itself is a developing country that still needs revolutionary things both in terms of education and this. This can be realized by the process implemented by educational institutions, whether it is a public education institution or in terms of creating more qualified human labor in the future.Keywords: History, Education, Islamic Boarding School